Effects of Profitability, Leverage, and Firm Size on Tax Avoidance of F&B Companies Listed on IDX - Fienda Kurniawati; Tri Utomo Prasetyo (Sekolah Tinggi Ilmu Manajemen YKPN Yogyakarta, 2023)
This study analyzes the effect of profitability, leverage, and firm size on tax avoidance. The research sample consisted of 13 manufacturing companies in the food and beverage sub-sector, determined using the purposive sampling method from 2019 to 2021. The data type used is secondary data in the form of annual financial statements. The data analysis technique uses panel data regression analysis. Based on the results of the study, it is proven that profitability has a significant positive effect on tax avoidance. Meanwhile, the impact of leverage and firm size on tax avoidance is not proven through the results of this study.